2018
DOI: 10.1007/s12088-018-0709-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pathogenicity of Fungal Pathogens Causing Black Point in Wheat on the North China Plain

Abstract: Fungi associated with black point were isolated from three highly susceptible wheat genotypes in the North China Plain. The 21 isolates represented 11 fungal genera. The most prevalent genera were (isolation frequency of 56.7%), (16.1%), and (6.0%). The other eight genera were, ,, ,, ,, and ; their isolation frequencies ranged from 0.8 to 4.8%. The pathogenicity of the isolates was individually assessed in the greenhouse by inoculating wheat plants with spore suspensions. Ten of the 21 isolates caused signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 24 publications
3
25
0
4
Order By: Relevance
“…It remains to be determined whether black point is primarily pathogen-induced ( Southwell et al, 1980 ; Rees et al, 1984 ; Conner et al, 1996 ; Kumar et al, 2002 ) or induced by environmental conditions ( Conner and Davidson, 1988 ; Conner, 1989 ; Conner et al, 1992 ; Fernandez et al, 1994 ; Kumar et al, 2002 ; Moschini et al, 2006 ; Walker, 2011 ). Our previous study indicated that pathogens could significantly increase the incidence of black point ( Xu et al, 2018 ), and the incidence was also affected by environmental variations between different years ( Li et al, 2019a,b ). It seems that the pathogen causes black point, and the appropriate environmental conditions will enhance the severity of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It remains to be determined whether black point is primarily pathogen-induced ( Southwell et al, 1980 ; Rees et al, 1984 ; Conner et al, 1996 ; Kumar et al, 2002 ) or induced by environmental conditions ( Conner and Davidson, 1988 ; Conner, 1989 ; Conner et al, 1992 ; Fernandez et al, 1994 ; Kumar et al, 2002 ; Moschini et al, 2006 ; Walker, 2011 ). Our previous study indicated that pathogens could significantly increase the incidence of black point ( Xu et al, 2018 ), and the incidence was also affected by environmental variations between different years ( Li et al, 2019a,b ). It seems that the pathogen causes black point, and the appropriate environmental conditions will enhance the severity of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The fungal isolate Ta-BP33, representing B. sorokiniana ( Xu et al, 2018 ), was cultured on Potato Dextrose Agar (PDA) medium in 9-cm Petri dish and incubated for 10–12 days in a dark growth chamber at 25 ± 1°C. Conidial suspensions were prepared according to the procedure described by Mahto et al (2011) , and the inoculation was as previously reported ( Li et al, 2019b ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations